The Effect of Customer-Oriented on Customer E-Satisfaction Through E-Service Quality as a Mediating Variable - Hanartyo, Ernawan Dwi; Tantiana, Wahyu (Yayasan Gema Bina Nusantara, 2025)
In today's digital era, the rapid development of information technology has made it essential to foster customer satisfaction. This study aims to examine the effect of customer orientation on e-customer satisfaction in the context of online services or e-commerce, specifically Shopee. It also evaluates whether e-service quality can mediate the relationship between customer orientation and e-customer satisfaction. Furthermore, the results of this study are expected to provide recommendations for Shopee in enhancing customer orientation and e-service quality, there by improving customer satisfaction. The sampling technique used in this study is purposive sampling. The population in this study consists of Shopee customers located in the Jakarta area. This quantitative study uses the structural equation model (SEM) method with SmartPLS as the analysis tool. The findings of this study indicate that both customer orientation and e-service quality significantly positively affect e-customer satisfaction. Additionally, e-service quality mediates the relationship between customer orientation and customer satisfaction. Moreover, the study reveals that the direct effect of customer orientation on e-customer satisfaction is stronger than the indirect effect through e-service quality as a mediating variable.